Mapping The Eq-5d-3l Utility Score From Pedsql™ 4.0 Generic Core Scale In Pediatric Transfusion-Dependent Thalassemia In Malaysia - Narindar, Irwinder Kaur Chhabra (2020)
The objective of this study was to map the non-preference based PedsQL Generic Core Scales instrument onto the EQ- 5D-3L utility score in a population of paediatric transfusion-dependent thalassemia(TDT) patients and determine the impact of using these mapped utility values on the cost effectiveness outcome of iron chelating therapy.